มาตรการทางกฎหมายเกี่ยวกับกิจการโรงแรม - อภิญญา เกษตรเอี่ยม (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Nowadays, hotel business including temporary accommodation play a major role in developing and promoting the tourism of Thailand. The Thai government should have a policy to regulate hotel business for the result of achieving the international standard and the safety of customers. This thesis has an objective to study and analyze the laws and regulations relating to hotel business in the aspect of their practicalities to the present situation. Moreover, this thesis also studies the limitation of doing hotel business and tries to make an assumption to solve the problems from the laws and regulations relating to hotel business in the long run. From my research, I have found that the laws and regulations relating to hotel business especially Hotel Act B.E.2478 is inconsistent with the situation of doing hotel business in Thailand. For instance, the regulations relating to the license procedure have many difficulties in obtaining license and its content about punishment is very below from the optimal standard. Besides, the laws relating to hotel business are not efficient to control other temporary accommodations such as guest house whose services are similar to hotel business. Due to the unsuitable standard of granting license for hotel business, the entrepreneurs in hotel business could not abide by the laws and regulations relating to hotel business. Then, the enforcement of the laws relating to hotel business has been a cronic problem until now. Accordingly, I fully support the revision of Hotel Act B.E.2478 and regulations relating to hotel business 1 for instance Building Control Act B.E.2522 1 Public Health Act B.E. 2535 to make the entrepreneurs in hotel business and temporary accommodation fully agreeable to abide by the laws and regulations relating hotel business. By setting the standard about the service, location , size ,and accommodation of hotel business , hotel business will be controlled by the Thai government optimally.